2014
DOI: 10.1038/jes.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of expert assessment based on airborne and urinary measures of nickel and chromium exposure in the electroplating industry

Abstract: The reliability and validity of six experts’ exposure ratings were evaluated for 64 nickel-exposed and 72 chromium-exposed workers from six Shanghai electroplating plants based on airborne and urinary nickel and chromium measurements. Three industrial hygienists and three occupational physicians independently ranked the exposure intensity of each metal on an ordinal scale (1–4) for each worker's job in two rounds: the first round was based on responses to an occupational history questionnaire and the second ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
3
2
1
Order By: Relevance
“…Overall, agreement (ICC1 and ICC3) between expert assessors was fair to good and was generally better than the agreement of non-experts, although CIs largely overlapped. This is, in general, comparable with that found in other studies (Goldberg et al, 1986;Kromhout et al, 1987;Macaluso et al, 1993;de Cock et al, 1996;Stewart et al, 2000;Mannetje et al, 2003;Walker et al, 2003;Steinsvag et al, 2007Steinsvag et al, , 2008Chen et al, 2014), although these also showed that agreement differs between agents, industries, and individual experts, which is something we could take into account to a small degree (e.g. cotton industry versus others).…”
Section: Discussion a Nd Con Clus Ionsupporting
confidence: 91%
See 4 more Smart Citations
“…Overall, agreement (ICC1 and ICC3) between expert assessors was fair to good and was generally better than the agreement of non-experts, although CIs largely overlapped. This is, in general, comparable with that found in other studies (Goldberg et al, 1986;Kromhout et al, 1987;Macaluso et al, 1993;de Cock et al, 1996;Stewart et al, 2000;Mannetje et al, 2003;Walker et al, 2003;Steinsvag et al, 2007Steinsvag et al, , 2008Chen et al, 2014), although these also showed that agreement differs between agents, industries, and individual experts, which is something we could take into account to a small degree (e.g. cotton industry versus others).…”
Section: Discussion a Nd Con Clus Ionsupporting
confidence: 91%
“…These results further indicate that agreement between assessors does not increase with the amount of information available to the rater. This has been observed previously in a number of industries (Post et al, 1991;de Cock et al, 1996;Stewart et al, 2000;Friesen et al, 2011;Chen et al, 2014), but is not universally true as for general population studies, small improvements have been observed when more information became available to the raters (Tielemans et al, 1999;Mannetje et al, 2003). What is of specific interest in this study, however, is the clear dip in agreement for medium information (compared with little and much detail) that can be observed especially for the experts but also for the non-experts, which has not been observed before.…”
Section: Discussion a Nd Con Clus Ionsupporting
confidence: 79%
See 3 more Smart Citations